2019
DOI: 10.3390/genes10020079
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assembly and Annotation of the Trichoplusia ni Tni-FNL Insect Cell Line Enabled by Long-Read Technologies

Abstract: Background: Trichoplusia ni derived cell lines are commonly used to enable recombinant protein expression via baculovirus infection to generate materials approved for clinical use and in clinical trials. In order to develop systems biology and genome engineering tools to improve protein expression in this host, we performed de novo genome assembly of the Trichoplusia ni-derived cell line Tni-FNL. Methods: By integration of PacBio single-molecule sequencing, Bionano optical mapping, and 10X Genomics linked-read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Bacteria were cultured in Dynamite medium for protein expression ( Taylor et al, 2017 ). SPRED1 was expressed in the baculovirus expression vector system using Tni-FNL cells ( Talsania et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria were cultured in Dynamite medium for protein expression ( Taylor et al, 2017 ). SPRED1 was expressed in the baculovirus expression vector system using Tni-FNL cells ( Talsania et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pooling and Illumina sequencing of all barcoded oligos and computationally linking all oligos taken from the same DNA molecule using the bespoke Supernova assembly tool [20] provides a new powerful approach for using short-read technologies in de novo genome assembly. This method has previously been applied to insect genomes with varying levels of success [21,22]. This is probably partly because this entire methodology is optimized around human genomes and genomes of similar size, while for genomes of significantly smaller sizes, optimization of assembly parameters is needed [20].…”
Section: Introductionmentioning
confidence: 99%
“…Though our earlier study identified Tni_contig_27 and Tni_contig_21 into AcMNPV genomes purified from T. ni larvae, we were unable to trace the origin of these TEs because no WGS was available for T. ni at the time ( Gilbert et al 2016 ). A BlastN similarity search for these TEs against the two now available T. ni genomes ( Chen et al 2019 ; Talsania et al 2019 ) revealed no hit. This result suggested the presence of Tni_contig_27 and Tni_contig_21 in the G0 AcMNPV population purified from T. ni larvae did not result from transposition of TEs located in the T. ni genome.…”
Section: Resultsmentioning
confidence: 99%